KARAKTERISTIK NUGGET YANG DIBUAT DENGAN VARIASI RASIO JAMUR MERANG (Volvariella volvaceae) DAN TEPUNG KORO PEDANG (Canavalia ensiformis L.) - Nurud Diniyah; Ahmad Nafi'; Zakiyatul Fachirah (Faculty of Agricultural Technology, University of Jember, 2015)
The aim of this study was to determine the effect of rasio mushroom and jack bean flour on the physical, chemical and organoleptic characteristic in the nugget product. This study used a randomized block design with one factor and triplet. Ratio mushroom and jack bean flour consists of P1 (100% : 0% ), P2 (90% : 10% ), P3 (80% : 20% ), P4 (70% : 30% ), and P5 (60% : 40% ). Different treatment showed significant differences in lightness, texture, moisture, ash, protein, carbohydrate and fiber content but not significant in fat content. The best treatment showed that P4 (mushroom 70 % : jack bean flour 30 %) has characteristic of lightness 42,95; texture 183,33 g/5mm; moisture 53,69%; ash 2,52%; fat 3,88%;, protein 12,52%; carbohydrate 27,39% and fiber 13,37%.Keywords: jack bean, mushroom, nugget